Innovating, gaining market share and fostering social inclusion : success stories in SME development (UN ECLAC, IDB & OAS SantiagoCL, 2011)
Seeks to put experiences for promoting growth and prosperity at the service of countries participating in Pathways to Prosperity in the Americas as they work to improve the living standards of their citizens. Highlights cases that stand out for their potential impact, their replicability in a variety of socio-economic and cultural contexts, their economic efficiency or their capacity to promote sustainable development. Includes not only lessons learnt iin the participating countries but also pinpoints replicable best practices in member countries of the participating institutions and in the rest of the world as well.
Keywords: SMALL ENTERPRISES